Production of ”Tokolan” White Shrimp Litopenaeus vannamei in the Cage with Different Rearing Density - Supriyono, E.; Purwanto, E.; Utomo, N.B.P. (Indonesian Society of Scientific Aquaculture (ISSA), 2006)
Larva rearing is one of the efforts to increase white shrimp Litopenaeus vannamei seed quality. This study was conducted to determine effect of rearing density on the quality and productivity of white shrimp larvae in cage system. The tested rearing densities were 500, 1000, 1500 and 2000 ind/m2 and cultured for 28 days. The result showed that rearing density did not affect survival rate and coefficient of variation of shrimp length. The treatmentonly affected the shrimp larvae growthwhere 500 ind/m2 rearing density gave the best growth. Keywords: white shrimp, larva, rearing density, net cage ABSTRAK Penokolan merupakan salah satu usaha untuk meningkatkan kualitas benih udang vaname (Litopenaeus vannamei). Penelitian ini dilakukan untuk mengetahui pengaruh padat tebar terhadap kualitas dan produktivitas pemeliharaan larva udang vaname di hapa. Padat tebar yang diuji meliputi 500 ,1000, 1500 dan 2000 ekor/m2 selama 28 hari pemeliharaan. Hasil penelitian menunjukkan bahwa padat tebar tidak mempengaruhi kelangsungan hidup dan koefisien keragaman panjang udang, dan hanya mempengaruhi pertumbuhan. Kepadatan 500 ekor/m2 menghasilkan pertumbuhan terbaik. Kata kunci: vaname, larva, kepadatan, hapa